Comparing the Efficacy of Biofeedback and Balloon-Assisted Training in the Treatment of Dyssynergic Defecation - Abbs Ali Pourmomeny; Mohammad Hassan Emami; Mahboobeh Amooshahi; Peyman Adibi (Canadian Journal of Gastroenterology)
BACKGROUND: Dyssynergic defecation does not respond appropriately to routine treatments for constipation. Recently, research has shown that biofeedback therapy is useful in anorectal dyssynergia.